Comparison of post-operative acidemia after intraoperative administration of balanced crystalloid plasma – Lyte A® vis-a-vis 0.9% sodium chloride in gastrointestinal surgery at a tertiary care hospital in Eastern India - Arindam Kumar Das; Sankar Roy; Bidyutbikas Gharami; Arunava Biswas; Dipasri Bhattachariya (Asian Journal of Medical Sciences, 2023)
Background: Fluid therapy is the most challenging and debatable aspect of perioperative care. Choice of administrating intravenous fluid perioperative period varies considerably among anesthesiologist.